2017
DOI: 10.1001/jama.2016.12819
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Screening Pelvic Examination

Abstract: IMPORTANCE Recent changes in the periodicity of cervical cancer screening have led to questions about the role of screening pelvic examinations among asymptomatic women.OBJECTIVE To systematically review literature on health benefits, accuracy, and harms of the screening pelvic examination for gynecologic conditions for the US Preventive Services Task Force (USPSTF).DATA SOURCES MEDLINE, PubMed, and Cochrane Central Register of Controlled Trials for relevant English-language studies published through January 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…Potential harms include false positives leading to diagnostic workups that could include surgery (in 5% to 36% of the 1 to 8% of women with positive screening tests) (16). Their draft recommendation stated that evidence was insufficient to assess the balance of benefits and harms, thus they could not recommend for or against performing screening pelvic examinations.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential harms include false positives leading to diagnostic workups that could include surgery (in 5% to 36% of the 1 to 8% of women with positive screening tests) (16). Their draft recommendation stated that evidence was insufficient to assess the balance of benefits and harms, thus they could not recommend for or against performing screening pelvic examinations.…”
Section: Commentmentioning
confidence: 99%
“…In 2016, a systematic review commissioned by the U.S. Preventive Services Task Force (USPSTF) was published that found inadequate evidence concerning the benefits and harms of screening pelvic examinations. Potential harms include false positives leading to diagnostic workups that could include surgery (in 5% to 36% of the 1 to 8% of women with positive screening tests) (16). Their draft recommendation stated that evidence was insufficient to assess the balance of benefits and harms, thus they could not recommend for or against performing screening pelvic examinations.…”
Section: Commentmentioning
confidence: 99%
“…In 2017, the US Preventive Services Task Force (USPSTF) released a statement about the use of pelvic exams in primary care, “the current evidence is insufficient to assess the balance of benefits and harms of performing screening pelvic examinations in asymptomatic, non-pregnant adult women” [ 44 ] after a systematic review of available clinical evidence [ 45 ]. In this review, there was no trials examined the effectiveness of the pelvic examination in reducing all-cause mortality and reducing cancer.…”
Section: Screening Of Gynecologic Cancer: Periodic Pelvic Examinationmentioning
confidence: 99%
“…12 A recommendation by the US Preventive Services Task Force (USPSTF) that followed the review concluded that current evidence is insufficient to assess the balance of benefits and harms of performing screening pelvic examinations. 13 The USPSTF believes that statements of insufficient evidence should prompt clinicians to explain to patients the uncertainty about the balance of benefits and harms if the service is offered.…”
Section: Commentmentioning
confidence: 99%
“…A systematic review commissioned by the Agency for Healthcare Research and Quality reiterated a lack of evidence of benefit and better characterized harms of screening pelvic examinations, at least in the context of ovarian palpation; abnormal results can be expected in 1.2–8.7% of those screened, leading to surgical exploration in up to 36% of those with positive testing. 12 A recommendation by the US Preventive Services Task Force (USPSTF) that followed the review concluded that current evidence is insufficient to assess the balance of benefits and harms of performing screening pelvic examinations. 13 The USPSTF believes that statements of insufficient evidence should prompt clinicians to explain to patients the uncertainty about the balance of benefits and harms if the service is offered.…”
Section: Commentmentioning
confidence: 99%